2013
DOI: 10.1227/neu.0b013e31827d1161
|View full text |Cite
|
Sign up to set email alerts
|

Stereoelectroencephalography

Abstract: SEEG is a safe and accurate procedure for the invasive assessment of the epileptogenic zone. Traditional Talairach methodology, implemented by multimodal planning and robot-assisted surgery, allows direct electrical recording from superficial and deep-seated brain structures, providing essential information in the most complex cases of drug-resistant epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
176
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 467 publications
(191 citation statements)
references
References 75 publications
9
176
5
1
Order By: Relevance
“…Thus, it can be expected that the absolute accuracy in future clinical trials will be degraded due to the above listed factors. This has already been confirmed by recent clinical case studies with the Neuromate [2] and ROSA [3], [16] robotic systems.…”
Section: Experimental Setup -Phantom Trialssupporting
confidence: 64%
See 2 more Smart Citations
“…Thus, it can be expected that the absolute accuracy in future clinical trials will be degraded due to the above listed factors. This has already been confirmed by recent clinical case studies with the Neuromate [2] and ROSA [3], [16] robotic systems.…”
Section: Experimental Setup -Phantom Trialssupporting
confidence: 64%
“…8 and in Table 3. Targeting errors are shown for two different target groups: superficial (1) and deep (2). This classification is related to the z-coordinate of the target in the coordinate system of the rigid fiducial marker or in the coordinate system of freely distributed individual spherical fiducials.…”
Section: Experimental Setup -Phantom Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardinale et al suggested a 3mm safety margin from cerebral vasculature 53. Computer‐assisted planning algorithms increase safety and reduce the time taken (see Fig 2).…”
Section: Presurgical Investigationsmentioning
confidence: 99%
“…Intracerebral S‐EEG data were recorded from 7 patients (5 males, 2 females; mean age = 28.0 ± 7.1 years) with drug‐resistant focal epilepsy who underwent S‐EEG during a presurgical evaluation 8. Informed written consent was obtained from all patients in accordance with the hospital's ethical committee policy (Niguarda Cà Granda Hospital, Milan, Italy).…”
Section: Methodsmentioning
confidence: 99%